Pengaruh Efek Stressor, Kepuasan Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Cipta Krida Bahari (Logistik) - Muhammad Nur Rahman; Mohammad Wahyu Wardhana; Linda Permanasari (P3M Politeknik Negeri Banjarmasin, 2022)
This study aims to see the effect of the independent variables Stressor, Job Satisfaction, anhandleEnvironment on the dependent variable of employee performance with the object of employees being PT Cipta Krida Bahari, a company engaged in integrated logistics services that handles the energy industry sector, especially oil and gas, management, warehousing, mining. , heavy equipment, power generation, and construction. The method used in this research is descriptive quantitative. with a sample of 25 people. Sampling was done by simple random sampling technique and data collection techniques were carried out in the form of questionnaires and observations. And the data analysis technique in this study used multiple linear regression, partial test (t), simultaneous test (f), and coefficient of determination test (R2). The results of the study obtained that two variables have a significant positive effect on employee performance, namely the variable job satisfaction and work environment, while the stressor variable has no significant effect. If the stressor variable increases, the employee's performance will decrease. Taken together, the three variables have a positive effect on employee performance and contribute to the effect of 84.5% while the remaining 15.5% is influenced by other variables outside of this study.